2008
DOI: 10.1158/1535-7163.mct-08-0299
|View full text |Cite
|
Sign up to set email alerts
|

Trichostatin A up-regulates p73 and induces Bax-dependent apoptosis in cisplatin-resistant ovarian cancer cells

Abstract: Several studies in the last years evidenced that deregulation of proapoptotic and antiapoptotic pathways are key players in the onset and maintenance of chemoresistance in advanced ovarian cancers. To characterize the signaling events and molecules involved in the acquisition of cisplatin resistance, we used the human ovarian cancer cell line A2780 and its derivative cisplatin-resistant subline A2780 CIS. We found that the mitochondrial intrinsic apoptotic pathway, induced by cis-dichlorodiammineplatinum (CDDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 47 publications
(37 reference statements)
4
42
0
Order By: Relevance
“…Interestingly, HDAC inhibitors also induce p21 expression in a p53-independent manner (51). In addition, a recent study showed that despite of induction of p53 upon TSA treatment, up-regulation of p73 contributes to TSA-induced Bax and apoptosis in A2780 ovarian cancer cells (52). Here, we found that like in MCF7 and MCF10A cells containing wide-type p53, DEC1 overexpression or TSA treatment increases ⌬Np63 expression in HaCaT cells containing a mutant p53 (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, HDAC inhibitors also induce p21 expression in a p53-independent manner (51). In addition, a recent study showed that despite of induction of p53 upon TSA treatment, up-regulation of p73 contributes to TSA-induced Bax and apoptosis in A2780 ovarian cancer cells (52). Here, we found that like in MCF7 and MCF10A cells containing wide-type p53, DEC1 overexpression or TSA treatment increases ⌬Np63 expression in HaCaT cells containing a mutant p53 (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…A recent report showed that HDAC inhibitors induced apoptosis in cells of cisplatin-resistant ovarian cancer associated with overexpression of Bad [36] . Moreover, Muscolini et al also reported that an HDAC inhibitor overcome apoptosis resistance to cisplatin by restoring both p73 and Bax [15] . These results demonstrate that HDAC inhibitors overcome resistance to cisplatin by up-regulating the expression of apoptosis-inducing factors.…”
Section: Discussionmentioning
confidence: 99%
“…It was originally isolated from Streptomyces hygroscopicus and identified as a fungistatic antibiotic that inhibits all class I and II HDACs. TSA can alter the expression of 2%-5% of genes [14] and can act as a chemo-sensitizer in cells of ovarian cancer, gastric cancer, and erythroleukemia [15][16][17] . Although the hyperacetylation of histones following inhibition of HDAC activ- [18][19][20][21] , the molecular mechanisms of TSA-sensitized cytotoxicity to chemotherapeutic drugs remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Bax-luciferase reporter construct was obtained by subcloning the PCR-generated fragment (Ϫ715 to Ϫ317 bp) from the bax gene promoter into BglII-HindIII sites of the pGL3-luciferase Enhancer vector (Promega) (19). The HA-tagged ubiquitin (HA-Ub) expression vector, carrying a fusion protein formed by an epitope of the HA and the entire open reading frame of the ubiquitin between the CMV enhancer and promoter and the SV40 polyadenylation signal, has been previously described (27).…”
Section: Methodsmentioning
confidence: 99%
“…This mutation was generated by the substitution AAG/AAT in heterozygosis. Although K351N mutation did not affect p53 expression, it was associated to the acquisition of resistance to apoptosis in A2780 CIS, particularly to defects in both cis-dichlorodiammine platinum (CDDP)-induced Bax expression and associated mitochondrial membrane depolarization, cytochrome c release, and activation of caspase-3 (19). K351N substitution significantly reduced the thermodynamic stability of p53 tetramers without affecting the overall half-life of the protein.…”
mentioning
confidence: 91%